Further evidence of superluminal active galactic nuclei as γ‐ray sources. Issue 4 (18th May 2020) - Xiao, Hubing; Fan, Junhui; Rando, Riccardo; Zhu, Jingtian; Hu, Liangjun
Abstract: In our previous work in Xiao et al. (SCPMA, 2019, 62, 129811), we suggested that six superluminal sources could be γ ‐ray candidates, and in fact, five of them have been confirmed in the fourth Fermi ‐LAT source catalog (4FGL). In this work, based on the 4FGL, we report a sample of 229 Fermi detected superluminal sources (FDSs), including 40 new FDSs and 62 non‐FDSs. Thus, we believe that all superluminal sources should have γ ‐ray emissions, and superluminal motion could also be a clue to detect γ ‐ray emission from active galactic nuclei. We present a new approach of Doppler factor estimate through the study of the γ ‐ray luminosity ( L γ ) and of the viewing angle ( ϕ ).